Preface - Lis, Piotr (Research Papers in Economics and Finance, 2022)
Dear Readers,We are pleased to present the latest issue of the Research Papers in Economics and Finance published by the Poznań University of Economics and Business Press. We have selected five scientific papers that we consider important for the academic discussion, works which inspire and provide substantial added value.This issue opens with a theoretical paper written by Dr Karolina Nowak from the Poznań University of Economics and Business, Poland entitled On the Concept of Good with Continual Reference to Economy. What is the axiological background of collaborative consumption society? The authors of the article analyse selected examples of redefinition of the concept of good in the context of new social narratives and the grounding of certain beliefs related to the idea of degrowth and sharing economy. The understanding of good as the community of consumption, focused on degrowth and the future generations and awareness of limited resources, is not becoming more widespread. Sharing economy, which grew out of the opposition against the consumption “drive” and the narration of profit, in a way substantiates the need to possess and the idea of growth to which it stands in opposition.The second great paper entitled Entrepreneurship as an Occupational Choice has been written by Prof. Aleksandra Gaweł from the Poznań University of Economics and Business, Poland. The author of the article shows thatthe flows between proper entrepreneurs and quasi-entrepreneurs connected with decisions to either hire or lay off staff are crucial for moderating the occupational choice, and thus, lead to changes in the employment structure. The revival of the market situation prompts us to follow the path of proper entrepreneurship or to become employed persons, abandoning quasi-entrepreneurship. The recession of business opportunities, in turn, is the reason for the reduction of relevant entrepreneurs and the reduction of employment, leading to an increase in the number of quasi-entrepreneurs.The third paper entitled Impact of Government Spending and Corruption on Foreign Direct Investment in Indonesia has been written by Dr Adya Utami Syukri from STIE Tri Dharma Nusantara, Makassar, Indonesia and Basri Hasanuddin, Abdul Hamid Paddu, Sultan Suhab from Hasanuddin University, Makassar, Indonesia. The results of the study clearly show that the higher the corruption level in the country, the lower the investment inflow. Hence, postulates have been formulated for the Indonesian government to fight corruption in the country, which is a significant barrier to the development of the economy.The fourth original and topical paper written by Prof. Ryszard Barczyk, Dr Joanna Spychała, Dr Zuzanna Urbanowicz and Dr hab. Agnieszka Ziomek, prof. UEP from the Poznań University of Economics and Business, Poland is entitled What to look for to increase work added value? Remote work and perceived productivity: A study in Poland, Hungary and the Czech Republic. The authors have used surveys to identify factors determining perceived productivity of individual workers who perform their job remotely and to measure the importance of factors determining labour productivity. The authors proved that high stress, low employee control and limited communication with managers minimise the growth of remote work productivity, since social relationships at work are correlated with productivity. Nonetheless, work organisation traits such as the proper work environment, travel cost savings, access to technical assistance and a fast Internet connection remain positively related to remote work productivity.The fifth paper entitled Index of the cycle of money - the case of Poland has been written by Constantinos Challoumis from the National and Kapodistrian University of Athens in Greece. According to the results obtained,Poland is above the worldwide average index of the cycle of money. The author proved that Poland is a well-structured economy able to overcome an economic crisis.                  Yours faithfully,dr hab. Piotr Lis, prof. UEP, Editor in Chief